2001
DOI: 10.2165/00002018-200124050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chemotherapy- Induced Adverse Effects in the Treatment of Colorectal Cancer

Abstract: The anticancer agents fluorouracil, raltitrexed, irinotecan and oxaliplatin show limited efficacy in the treatment of colorectal cancer and may be associated with substantial toxicity. Therefore, the prevention and reduction of chemotherapy-induced adverse effects is of major significance, in accordance with the increasing concern for the quality of life of patients with cancer. Therapeutic drug monitoring of fluorouracil and chronomodulation of fluorouracil and oxaliplatin, have been effective in reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 100 publications
1
39
0
Order By: Relevance
“…Both 5-FU and CPT-11, currently used for this indication, are known to trigger digestive problems [50]. In the present study, the addition of Dbait displayed no local toxicity and induced no digestive problems, suggesting that it could be added to chemotherapy without causing any additional toxicity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Both 5-FU and CPT-11, currently used for this indication, are known to trigger digestive problems [50]. In the present study, the addition of Dbait displayed no local toxicity and induced no digestive problems, suggesting that it could be added to chemotherapy without causing any additional toxicity.…”
Section: Discussionsupporting
confidence: 54%
“…We have already demonstrated that Dbait administration does not increase the sensitivity of healthy tissues to irradiation in mice [50]. A phase I trial to evaluate the tolerance to local Dbait administration in association with radiotherapy in in-transit metastases of melanoma is currently underway (DNA therapeutics, data on file).…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide is another potential drug that may reduce CID [14,25,33,34,57,60]. It works by acting on the epithelial cells, inhibiting gut hormones such as serotonin, vasoactive intestinal peptide and gastrin, as well as increasing intestinal transit time, promoting absorption of electrolytes through the intestine and decreasing mesenteric blood flow, secretion of fluids and electrolytes [34,57,77].…”
Section: Octreotidementioning
confidence: 99%
“…It works by acting on the epithelial cells, inhibiting gut hormones such as serotonin, vasoactive intestinal peptide and gastrin, as well as increasing intestinal transit time, promoting absorption of electrolytes through the intestine and decreasing mesenteric blood flow, secretion of fluids and electrolytes [34,57,77]. There are a number of clinical trials which have shown that octreotide is effective in decreasing CID [14,25,33,34,57]. Recent clinical guidelines recommend that octreotide is administered at a dose of at least 100 mg subcutaneously twice a day [57] or upward titration of the octreotide dose until the symptoms of diarrhoea are controlled [5].…”
Section: Octreotidementioning
confidence: 99%
“…The oedema, which is an adverse outcome of chemotherapy administration [368] made it difficult to obtain an accurate sural nerve assessment.…”
Section: -197mentioning
confidence: 99%